2009
DOI: 10.1158/1078-0432.ccr-08-2690
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase-Specific Virotheranostics for Human Head and Neck Cancer

Abstract: Purpose: Long-term outcomes of patients with squamous cell carcinoma of the head and neck (SCCHN) remain unsatisfactory despite advances in combination of treatment modalities. SCCHN is characterized by locoregional spread and it is clinically accessible, making it an attractive target for intratumoral biological therapies. Experimental Design: OBP-301is a type 5 adenovirus that contains the replication cassette in which the human telomerase reverse transcriptase promoter drives expression of the E1 genes. OBP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The treatment field of radiotherapy includes primary tumors and regional lymph nodes. We previously showed that intratumorally injected OBP-301 expressing the GFP gene is effectively transported into the lymphatic circulation; viral replication produced GFP fluorescence signals in the metastatic lymph nodes in orthotopic human colorectal and oral cancer xenograft models (39,40). Therefore, we anticipate that intratumoral OBP-301 administration will radiosensitize both primary tumors and regional lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment field of radiotherapy includes primary tumors and regional lymph nodes. We previously showed that intratumorally injected OBP-301 expressing the GFP gene is effectively transported into the lymphatic circulation; viral replication produced GFP fluorescence signals in the metastatic lymph nodes in orthotopic human colorectal and oral cancer xenograft models (39,40). Therefore, we anticipate that intratumoral OBP-301 administration will radiosensitize both primary tumors and regional lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…We further modified OBP-301 to express the green fluorescent protein ( GFP ) gene for monitoring viral replication. The resultant adenovirus, designated OBP-401 (TelomeScan), efficiently labeled tumor cells with green fluorescence, enabling us to track viral spread in vivo 1314. Preclinical as well as clinical studies have demonstrated successful virus spread, including spread to the regional lymphatic areas, and promising antitumor effects were shown with intratumoral administration of the virus1516.…”
mentioning
confidence: 99%
“…We previously reported that intratumoral injection of a telomerasespecific replication-competent adenovirus Telomelysin suppressed the growth of a subcutaneous xenograft tumor (10) and of lymph node metastasis of an orthotopic colorectal cancer model (17,25). Moreover, an GFP-expressing Telomelysin (OBP-301, TelomeScan) could induce tumor-specific GFP accumulation in the metastatic regions at lymph nodes (13,26), liver (27), and peritoneal cavities (28) of colorectal tumor-bearing mice. These findings strongly suggest that a TelomeKiller-based PDT strategy is a useful anticancer strategy to eliminate metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%